Prevalência de transtornos mentais comuns em trabalhadores da indústria da Bahia - Fonseca, Ilva Santana Santos (2012)
Studies of work and its relations with different social conditions and health of individuals has grown over time. Many of these have associated the more different occupations to health, including mental health, a topic that has led researchers around the world to conduct research on the influence of certain sociodemographic characteristics, psychological and occupational mental health. Despite the growth of this research work involved is still very little quantitative studies involving mental health and industrial workers, especially involving the occupational groups according to the Brazilian Classification of Occupations (CBO). So, facing this reality, this study sought to describe the profile of the industrial population of Bahia, according to the sociodemographic and labor and to estimate the prevalence of common mental disorders among industrial workers in Bahia. This was a study in Bahia among industrialists in the period 2008 to 2009. Were considered eligible registered industrial workers during the survey, comprising 59,477 employees and 41,639 had their valid data in Health Risk Management System in Industry (SGRSI), representing 70.0% of the enrolled population. The highest percentage was in the group of industrialists GG7 (59.1%). According to sex, the group with higher percentage of men was the GG6 (96.8%) and women, GG2 (42.7%), marital status, married / stable union in the group GG2 (74, 4%) of singles in GG9 (43.4%) and divorced or widowed in GG6 (4.8%). GG3 The group had the highest percentage of those with primary education (74.7%), the group GG6 with high school (63.6%) and education (34.9%). Regarding age, the GG8 workers showed up to 25 years, GG9 in the range 25 to 45 years (68.3%), and GG1 with over 46 years (28.8%). With respect to income, most of that earned by a minimum wage were in gg4 (9.2%), 1 to 3 minimum wages in GG2 (92.3%) and workers in the GG6, more than 3 salaries (49 3%). Job characteristics, showed that industrial workers with more than six days of work and weekly working hours over 40 hours, were mostly in groups GG6 (36.5%) and GG8 (51.3%), respectively. Those who were not employed at the same time each day in GG5 (31.6%) and working for at least one day a week at night in GG6 (36.5%). To survey the prevalence of common mental disorders used the GHQ-12 that tracked 11.6% of disorders. The occupational group with the highest prevalence of disorders was gg4 (13.2%, PR = 1.3, p <0.05). Regarding the reference group (GG3), the difference being statistically significant. Through this study verifies the importance of more research in the conditions involving industrialists, the process and work organization, psychosocial factors and mental health of them, in order to track preventive and mental health promotion, and also able to reflect on how the classification of occupations among these workers.